2004
DOI: 10.1038/sj.cr.7290252
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression profiles of NIH3T3 cells regulated by human lung cancer associated gene CT120

Abstract: CT120, a novel membrane-associated gene implicated in lung carcinogenesis, was previously identified from chromosome 17p13.3 locus, a hot mutation spot involved in human malignancies. In the present study, we further determined that CT120 ectopic expression could promote cell proliferation activity of NIH3T3 cells using MTS assay, and monitored the downstream effects of CT120 in NIH3T3 cells with Atlas mouse cDNA expression arrays. Among 588 known genes, 133 genes were found to be upregulated or downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It has been reported that cathepsin B is required for reovirusmediated oncolysis, and transformed NIH3T3 cells are susceptible to the reovirus-mediated oncolysis, but normal NIH3T3 cells are not (Alain et al, 2007). Cathepsin B expression is significantly (more than 50 times) elevated by transformation of NIH3T3 cells (Chambers et al, 1992;He et al, 2004). These results suggest that cathepsin B activity in normal NIH3T3 cells is negative or much lower than that in transformed NIH3T3 cells, consistent with our result.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that cathepsin B is required for reovirusmediated oncolysis, and transformed NIH3T3 cells are susceptible to the reovirus-mediated oncolysis, but normal NIH3T3 cells are not (Alain et al, 2007). Cathepsin B expression is significantly (more than 50 times) elevated by transformation of NIH3T3 cells (Chambers et al, 1992;He et al, 2004). These results suggest that cathepsin B activity in normal NIH3T3 cells is negative or much lower than that in transformed NIH3T3 cells, consistent with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Fam57A (CT120), a membrane-associated gene important for amino acid transport (35), was found to be 2.6- and 2.5-fold downregulated in DDLS8817 and LPS141, respectively. CT120 has been implicated in lung carcinogenesis and its ectopic expression in NIH3T3 cells has been associated with Raf/MEK/Erk and PI3K/Akt signaling pathways driving cell proliferation, cell survival, and anti-apoptotic pathways (36). EIF3M, eukaryotic initiation factor 3 subunit M, is an essential gene for global cellular protein synthesis and polysome formation and appears to be associated with the bulk of cellular mRNAs (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that knocking down CT120 in SPC-A-1 cells results in reduced in vitro cell growth rate and in a decrease of tumorigenicity in nude mice 7 , 14 . In addition to these findings the study revealed that proliferation of the NIH3T3 and A549 cells is promoted by CT120 expression 7 , 12 .…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, it has also been shown that CT120A is expressed in various tumor cell lines and its expression is significantly higher in lung cancer than in control tissue or in normal lung tissue 7 . He et al 12 also reported that ectopic CT120 gene expression in the NIH3T3 cells activates two major signaling pathways which are involved in cell proliferation, survival and apoptosis. Silencing of CT120A results in reduced cell growth rates and tumorigenicity in nude mice and in tumor cell lines 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%